2010
DOI: 10.1007/s00167-010-1127-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of a medial knee reconstruction with comparison of bioabsorbable interference screw constructs and optimization with a cortical button

Abstract: Current fixation techniques in medial knee reconstructions predominantly utilize interference screws alone for soft tissue graft fixation. The use of concurrent fixation techniques as part of a hybrid fixation technique has also been suggested to strengthen soft tissue fixation, although these hybrid fixation techniques have not been biomechanically validated. The purpose was to biomechanically evaluate two distal tibial superficial MCL graft fixation techniques that consisted of an interference screw alone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
0
13
1
Order By: Relevance
“…A suture anchor was placed at this location and the graft was secured at this site, which restored the native proximal tibial attachment of the superficial medial collateral ligament. The strength of the suture anchor reconstruction graft fixation was reportedly comparable to that of the native strength of the proximal division attachment on the tibia [12]. At this point, the knee was flexed to the point where it appeared any concurrent repaired tissues could be maximally flexed to determine the ''safe zone'' ROM, which could be initiated on Postoperative Day 1.…”
Section: Surgical Techniquementioning
confidence: 99%
“…A suture anchor was placed at this location and the graft was secured at this site, which restored the native proximal tibial attachment of the superficial medial collateral ligament. The strength of the suture anchor reconstruction graft fixation was reportedly comparable to that of the native strength of the proximal division attachment on the tibia [12]. At this point, the knee was flexed to the point where it appeared any concurrent repaired tissues could be maximally flexed to determine the ''safe zone'' ROM, which could be initiated on Postoperative Day 1.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Previous studies do not report moment to failure for soft tissue graft reconstruction, but cyclical submaximal loading demonstrated that the construct had sufficient stability to allow early preoperative rehabilitation. 29 Future study using cyclical testing at submaximal loads may yield additional information about the internal brace construct. Unfortunately, time-zero conclusion Posteromedial knee repair with internal bracing is superior to repair alone and is similar to allograft reconstruction for all parameters measured.…”
Section: Limitationsmentioning
confidence: 99%
“…1 Cortical suspensory fixation has been shown to provide fixation of soft-tissue grafts that is superior to interference screw fixation alone. 9 A particular benefit of this technique is the robust femoral fixation with the ACL Tightrope RT, as well as tibial fixation with either the staple leaving the distal insertion intact or an interference screw for a free graft. The ability to re-tension the graft after cycling the knee through a range of motion is particularly attractive.…”
Section: Discussionmentioning
confidence: 99%